Active Center Size-Dependent Fenton-Like Chemistry for Sustainable Water Decontamination - Zelin Wu; Zhaokun Xiong; Liu, Wen; Liu, Rui; Feng, Xuezhen; Bingkun Huang; Xinhao Wang; Yixuan Gao; Hong Chen; Gang Yao; Bo Lai (Environmental Science & Technology, 2023)
Accurately controlling catalytic activity and mechanism as well as identifying structure–activity–selectivity correlations in Fenton-like chemistry is essential for designing high-performance catalysts for sustainable water decontamination. Herein, active center size-dependent catalysts with single cobalt atoms (CoSA), atomic clusters (CoAC), and nanoparticles (CoNP) were fabricated to realize the changeover of catalytic activity and mechanism in peroxymonosulfate (PMS)-based Fenton-like chemistry. Catalytic activity and durability vary with the change in metal active center sizes. Besides, reducing the metal size from nanoparticles to single atoms significantly modulates contributions of radical and nonradical mechanisms, thus achieving selective/nonselective degradation. Density functional theory calculations reveal evolutions in catalytic mechanisms of size-dependent catalytic systems over different Gibbs free energies for reactive oxygen species generation. Single-atom site contact with PMS is preferred to induce nonradical mechanisms, while PMS dissociates and generates radicals on clusters and nanoparticles. Differences originating from reaction mechanisms endow developed systems with size-dependent selectivity and mineralization for treating actual hospital wastewater in column reactors. This work brings an in-depth understanding of metal size effects in Fenton-like chemistry and guides the design of intelligent catalysts to fulfill the demand of specific scenes for water purification.